Beyond Absurdity: Character Reinforcement in Bakdi Soemantos Short Stories - Novita Dewi (Soegijapranata Catholic University, 2016)
This article examines the absurd characters in Bakdi Soemantos selected short stories in the light of character reinforcement. Through the use of analogy of name, environment, and interlocking relationships among the characters, it is revealed that these characters reflect contemporary societys aspirations and expectation of their exemplary leaders or individuals with high authority. The presence of such weird but wise characters discloses the blurred boundaries of sanity and insanity in striving for life meaning as well as meaning of life